The perception of mothers about the volition of children with cerebral palsy for the engagement in everyday life occupations - Oliveira, Alyne Kalyane Câmara de (2014)
Volition, as the willingness to engage/performing daily activities, is considered a prerequisite of human doing. In children with special needs such as cerebral palsy (CP) who deal with deficits of sensorimotor control and musculoskeletal, the volition can work as an influential feature to their engagement in occupations. The family is an important mediator in the child´s volitional process. However, researches about influence of the volition of children with special needs are scarce. This study aimed to identify how mothers perceive and deal with the volition of the child with CP to perform daily activities in scholar, play and self-care areas. Participated six mothers of children with CP, between 6 and 9 years old, levels I and IV of the GMFCS in a school -health unit inside Paulista, who answered a semistructured interview based on The Volitional Questionnaire. Based on the analysis of the content, three topics emerged: a) mother’s perceptions about the volition of children; b) mothers’ perception regarding their role in the child´s volitional process and c) strategies used by mothers to encourage children to develop volition. Results showed that mothers perceive the relationship of the child volition versus involvement in activities and their importance in child´s volition for activities who judge relevant, mainly the formal school activities and self-care, with slightest consideration for the play. These mothers are looking for ways to implement the incentive, but they have revealed limited knowledge about strategies for stimulation of volition, showing the need for investments in health education for the guidance of those families.